2003
DOI: 10.1159/000067743
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of Renal Vasopressin V<sub>1A</sub> and V<sub>2</sub> Receptors in Spontaneously Hypertensive Rats

Abstract: To elucidate the role of arginine vasopressin (AVP) in a hypertensive state, the characteristics of renal cortex V1A and medulla V2 receptors in young spontaneously hypertensive rats (SHR) during the developmental phase of hypertension were compared with those of age-matched Wistar-Kyoto (WKY) rats using the radioligand receptor assay technique. The systolic blood pressure of 8-week-old SHR was statistically significantly higher than that of WKY rats (142 ± 1 vs. 125 ± 2 mm Hg). The plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 31 publications
1
9
1
Order By: Relevance
“…On the other hand, the change of ␣-ENaC was relatively minimal, with only a mild increase in the ISOM in 6-wk SHR. The changes in expression fit the previously described patterns seen in response to vasopressin treatment (17); because vasopressin levels and its responsiveness have been shown to be increased in SHR (13,27,42,53), the observed changes in expression are consistent with this view. Increased sodium reabsorption in the collecting duct is correlated with the increased protein abundance of ENaC subunits at the site of function, i.e., in the plasma membrane.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…On the other hand, the change of ␣-ENaC was relatively minimal, with only a mild increase in the ISOM in 6-wk SHR. The changes in expression fit the previously described patterns seen in response to vasopressin treatment (17); because vasopressin levels and its responsiveness have been shown to be increased in SHR (13,27,42,53), the observed changes in expression are consistent with this view. Increased sodium reabsorption in the collecting duct is correlated with the increased protein abundance of ENaC subunits at the site of function, i.e., in the plasma membrane.…”
Section: Discussionsupporting
confidence: 88%
“…The excessive retention of sodium in SHR may result from either a reduced glomerular filtration rate (GFR) (15,53) or an enhanced tubular reabsorption (40) or both. The activities of Na-K-ATPase and sodium/ hydrogen exchanger in the proximal tubule was found to be significantly higher in young SHR compared with age-matched Wistar-Kyoto rats (WKY) (21,40), and these changes may account in part for the increased ECF volume expansion in SHR.…”
mentioning
confidence: 99%
“…The importance of AVP and V 2 receptor signaling in the development of hypertension has been supported in SHR [10,11] . Indeed, the urine was more concentrated with its volume decreased in SHR in the present study.…”
Section: Discussionmentioning
confidence: 98%
“…The importance of AVP and V 2 receptor signaling in the development of hypertension has been also supported in spontaneously hypertensive rats (SHR) [10,11] . In addition, the urinary excretion and the renal expression of AQP2 are increased in SHR [5,7] .…”
Section: Introductionmentioning
confidence: 98%
“…We have previously shown that preglomerular arterioles of 8-wk-old SHR express approximately two-to three-times as many V 1a receptors normalized to milligram tissue protein as do vessels of age-matched WKY under euvolemic conditions (50), an observation recently confirmed (41). PCR analysis reveals that the reason for the elevated receptor number likely results due to twice the amount of V 1a mRNA (50).…”
Section: Discussionmentioning
confidence: 70%